A study on the Neighborhood Street characteristics of housing regeneration in original part of Seongnam city Focused on the Taepyeong 2, 4 Area - - Cheol Lee, Ki; Lee, Young (International Journal of Engineering and Technology, 2019)
Recently, the plans to revitalize the deteriorated residential districts in the Built-up area of Seongnam have been turned into more sustainable and systematic plans through gradual urban regeneration projects instead of overall pulling down the whole block. This is because paradigm in urban regeneration has been shifted from a uniform reconstruction method for existing deteriorated residential areas to the enhancement in the awareness of these existing areas as familiar settlements and the right of residents. The Built-up area of Seongnam was formed on a hilly area since the early 1970s and has been a major target of reconstruction and redevelopment till now because most of the present residential areas are deteriorated excessively. Due to the sustainable urban regeneration policy which has begun in the late 2000s centering in the capital area, some blocks designated as reconstruction and redevelopment areas were released with sustainable urban regeneration plans so that the residential areas environments are beginning to be improved.This study judges that the Neighborhood Streets in the Built-up area are the most important planning elements for Housing Re-generation of the deteriorated residential areas in Seongnam. Despite that the walking environments in the built-up area in Seongnam are poor because of being formed in steep hilly areas, however, neighborhood commercial facilities are activated along Neighborhood Streets in the Built-up area of Seongnam. Those commercial facilities were not built as pre-planned but were spontaneously formed along these streets activated in residential areas. In this study, ‘Neighborhood Street in the Built-up area’ is proposed as main indicator that can be used to maintain and supplement the order of existing urban fabric when deteriorated residential areas are regenerated through gradual improvement plan of residential environments in existing urban areas. Therefore, the existing Neighborhood Streets in the Built-up area are defined as the major community constituent factor in the Built-up area in Seongnam and the usability of the Neighborhood Streets will be grasped.
Keywords: Housing Regeneration; Built-up area; Deteriorated Residential area; Neighborhood Street; Neighborhood Facilities